All my companions are free, I alone am excepted : a socio-economic history of recaptured Africans at the Cape Colony in the age of reform, c. 1807-1834 - Crous, Benjamin Daniel (Stellenbosch : Stellenbosch University, 2024)
Thesis (MA)--Stellenbosch University, 2024.